Pengadaan dan Investasi Menggunakan LPSE Pada Pemilihan Kebutuhan Perangkat IT Menggunakan Metode TOPSIS - -, Ruben Dwijaya Setyo Atmojo; Stefanus Christian Gunawan; Soetam Rizky Wicaksono (Universitas Haji Sumatera Utara, 2024)
This study examines the method of procurement of IT equipment in the Indonesian National Army (TNI-AD) through the Electronic Procurement Service (LPSE). The use of LPSE aims to increase efficiency and transparency in the procurement process of goods and services, especially in the military sector. This research was carried out in several stages, starting from tracing the type of IT-based procurement of goods, identifying the equipment used, analyzing the criteria needed, calculating the TOPSIS method, to making a final report. The results of the study show that the use of LPSE provides several significant advantages, such as centralization of procurement data, increased competition between goods providers, and reduction of procurement process time. LPSE also allows for strict supervision and easier audits of the entire procurement process, which can later minimize the risk of abuse of authority and corruption. However, the study also identified several challenges in the implementation of LPSE, including the need for adequate IT infrastructure in various regions and the capacity building of the human resources involved. There are also challenges in terms of the integration of the LPSE system with the existing internal military system, which requires significant coordination and adjustment. Thus, continuous support from the government is needed to overcome this challenge and ensure maximum benefits from LPSE for the IT equipment procurement process in the TNI. The recommendations of this study include increased training for related personnel, improvement of IT infrastructure, and increased coordination between agencies to support better integration.